Cultural Barrier at the time of Menstruation: Perspective from Girl Students - Karki, Tej Bahadur; Khadka, Kalpana (Nepal Journal of Multidisciplinary Research, 2019)
Culture is man-made; one belief system originated with the human civilization. It has bounded the people within one common belief system. Culture determines the personality of people. Here, the main objective of this study is to find out the cultural barriers to girls at the time of menstruation. The study was conducted among the 120 girls of secondary level school. The study found that 50% girls reported that they were deprived to carry out the daily activities like cooking and fetching water and more than 80% girls shared that they were deprived to go in religious places at the time of menstruation. The result founds that still the cultural practices have created the stigma and discrimination towards the girls at the time of menstruation which has direct effect in their personal and professional growth and development as well as it has also significantly affected in the menstrual hygiene management. So, there is need of massive awareness program to society about the negative impact of harmful cultural practices related to menstruation.